دراسة و تحليل الزمن الحقيقي في أنظمة الطاقة الكهربائية - هرموش زياد (Latakia University Journal -Engineering Sciences Series, 2016)
يهدف البحث إلى دراسة و تحليل الزمن الحقيقي في نظام الطاقة الكهربائية المؤلف من تجهيزات التوليد و النقل و التوزيع عن طريق إعادة توزيع الاستطاعة الفعلية للمولدات الكهربائية, بغية تقييد عمليات الإفراط في تحميل خطوط نقل الطاقة الكهربائية في الحالة التي يكون فيها حمولات المحطة الكهربائية الاحتياطية لا تغطي الأحمال الضرورية و الهامة عند العطل. تشير أغلب القوانين المتعلقة بتصميم نظم الطاقة الكهربائية إلى تناسب طردي للزمن الحقيقي لعمل تجهيزات نظام الطاقة الكهربائي مع الميزات التي تعطيها العلاقات الرياضية الناظمة لتوابع التوزيع الاحتمالية بالإضافة للطرق الإحصائية, و التي تعطي إمكانية كبيرة لدراسة و تحليل زمن التحليل الرياضي الحقيقي عند حساب الحمولات المعتبرة, و هذا ما يستتبع الوصول إلى الحلول المنشودة في الحد من الأضرار الناجمة عن الأعطال التي يمكن أن تحدث في أي وقت من الأوقات. The study seeks to determine the real time in electrical power system, which consists of generating, transmitting and distributing equipment by using redistributing active power of electrical generators in order to organizing the overload operation of electrical power transmission line loading in such case that the spare loads of electrical station are not covering the important and necessary loads at failures. The most of laws related to electrical power systems design indicated to proper ratio of real time of electrical power system equipment along with characteristics of probability distributed functions in addition to statistics methods which give a high possibility to reduce the real time of considered loads; so; this leads to the requested solutions which reduce the damage of failures at any time.